HUBUNGAN TINGKAT PENGETAHUAN MENOPAUSE DENGAN TINGKAT KECEMASAN PADA WANITA MENOPAUSE DI DESA NGABEYAN KECAMATAN KARTASURA KABUPATEN SUKOHARJO - Ningsih, Endang Dwi; Setyaningsih, Rahayu (Akademi Keperawatan Giri Satria Husada Wonogiri, 2016)
Introduction: Menopause is the last menstrual period experienced, usually will have a tough time include: difficulty sleeping, night sweats, emotions are difficult to control and so on, which increase to the effects of anxiety. With regard to the foregoing, the authors are interested in studying the